ELECTRONIC MONEY TRANSFER SYSTEMS AND BUSINESS PROCESS MANAGEMENT AMONG COMMERCIAL BANKS IN KENYA - Getembe, Kepha Nyankora; Magutu, Peterson Obara; Muro, Maxmillah Bituntu (European Scientific Journal, ESJ, 2013)
Conversion of ordinary business into e-business has forced organizations to be redesigned and reshaped. E-business is a combination of economic, technology and market forces that reinvented strategies of traditional business. The business process is counted to use the power of computers and communication networks which are known as Internet. This can allow organizations to stay competitive and more efficient. Also, new business models have been introduced and implemented in a variety of ways. Electronic banking, also known as electronic fund transfer (EFT), uses computer and electronic technology as a substitute for checks and other paper transactions. EFTs are initiated through devices such as cards or codes that you use to gain access to your account. The study intended to establish how value can be created in business management through electronic money transfer systems in commercial banks in Kenya. This complements an earlier study on money transfer systems in Tanzania and Uganda. This was a descriptive study where the researcher visited the selected commercial banks in Nairobi Area and asked them about the benefits of using EFT in their banks. The study targeted forty five (45) commercial banks in Kenya. Primary data were obtained using a self administered questionnaire. The data were analyzed using procedures within the Statistical Package for Social Sciences (SPSS), PC version 10. Out of 25 respondents targeted for this study 20 of them responded to the questionnaire giving a response rate of 80%. The study found out that the study found out that various ﻿short comings such as cost, long queues, losses as a result of foreign exchange and difficulty dealing with the technology of money transfer systems affected the value of business process management. Many respondents used money transfer systems because of the benefits associated with them. Among the most preferred benefits was efficiency while others that came in where reliability and speed. Most of the respondents were willing to bear any cost of an MTS as it was efficient. In addition of value to BPM, EFTs and direct debit were found to be of great importance. However the cost of MTS and other shortcomings associated with them were found to have a significant effect on the value of Business process management. The researchers recommend an improvement in the efficiency of electronic Money transfer Systems so as to reap the maximum benefits out of them in BPM.